2015
DOI: 10.1140/epjc/s10052-015-3818-6
|View full text |Cite
|
Sign up to set email alerts
|

Reducible gauge theories in very special relativity

Abstract: In this paper we analyze the tensor field (reducible gauge) theories in the context of very special relativity (VSR). Particularly, we study the VSR gauge symmetry as well as VSR BRST symmetry of Kalb-Ramond and Abelian 3-form fields involving a fixed null vector. We observe that the Kalb-Ramond and Abelian 3-form fields and corresponding ghosts get masses in the VSR framework. The effective action in VSR-type axial gauge is greatly simplified compared with the VSR-type Lorenz gauge. Further, we quantize these… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
8
0

Year Published

2017
2017
2018
2018

Publication Types

Select...
6

Relationship

3
3

Authors

Journals

citations
Cited by 14 publications
(8 citation statements)
references
References 44 publications
0
8
0
Order By: Relevance
“…Also, it has been shown that the gauge field in the quantum gauge perspective naturally acquires mass without the conventional Higgs mechanism [7]. The modifications due to VSR have also been analyzed for the reducible gauge theories using the BV formulation [8]. Within the VSR framework, the event space underlying the dark matter and the dark gauge fields supports the algebraic structure [9].…”
Section: Overview and Motivationmentioning
confidence: 99%
See 4 more Smart Citations
“…Also, it has been shown that the gauge field in the quantum gauge perspective naturally acquires mass without the conventional Higgs mechanism [7]. The modifications due to VSR have also been analyzed for the reducible gauge theories using the BV formulation [8]. Within the VSR framework, the event space underlying the dark matter and the dark gauge fields supports the algebraic structure [9].…”
Section: Overview and Motivationmentioning
confidence: 99%
“…Here we note that, in comparison to VSR-modified covariant gauges, the gauge-fixed Lagrangian density takes simplest form [8] in VSR-modified light-cone gauge, η · A = 0, where η μ is an arbitrary constant vector that defines a preferred axis in space. Now, the effective quantum Lagrangian density for Yang-Mills theory in VSR is given by…”
Section: Overview and Motivationmentioning
confidence: 99%
See 3 more Smart Citations